Evaluation of treatment options for Atlantic Canadian seafood processing plant effluent. Issue 4 (November 2013) - Jamieson, Bryan Lee; Gonçalves, Alex Augusto; Gagnon, Graham A.
Abstract : The purpose of this study was to evaluate different effluent treatment options for Atlantic Canadian seafood processing plants. Bench-scale testing with a 25-mesh screen, sedimentation (SED), and dissolved air flotation (DAF) was conducted. Treatment by SED and DAF was successful in reducing contaminant concentrations with maximum observed percent reductions: biochemical oxygen demand, BOD5 (90%); chemical oxygen demand, COD (60%); turbidity (99%); total suspended solids, TSS (95%); and ammonia nitrogen, NH3 -N (50%). Bench-scale 25-mesh screen runs for select effluent types showed poor reduction efficiencies and appeared to provide inadequate removal of contaminants. Sedimentation and DAF using alum were effective at removing solids but less effective at removing soluble effluent components. Improved performance may be possible with further treatment technology optimization on an effluent specific basis.